Clinical Presentation and Therapy of Primary Immune Thrombocytopenia Resistant to Splenectomy - Kara-Jovanović, Aleksandar; Suvajdžić-Vuković, Nada (International Journal of Medical Students, 2020)
Background: A satisfactory therapeutic response is achieved with splenectomy in 60–80% of the patients diagnosed with immune thrombocytopenic purpura (ITP). There is an ongoing consensus on the short-term efficacy of splenectomy, however, its long-term efficacy remains controversial. Our aim was to establish the frequency of resistance and relapse after splenectomy, the occurrence of complications, the therapeutic strategies and the drug efficacy in splenectomy-resistant ITP. Methods: We retrospectively analyzed 138 adult ITP patients who had been previously diagnosed and treated at the Clinic of Hematology, Clinical Center of Serbia, and who underwent splenectomy between 1987 and 2018. Results: Of the 138 ITP patients, 20.3% (n=28/138) were refractory to splenectomy, 11.6% (n=16/138) relapsed and 8.7% (n=12/138) were primarily resistant. The average post-splenectomy follow-up period was 117 months (range 3-474). The average follow-up period of the patients resistant to splenectomy was 147 months (range 23-474). Of the patients refractory to splenectomy, 67.8% (n=19/28) showed a good therapeutic response: 49% (n=14/28) complete remission and 18.8% (n=5/28) partial remission. The response was usually achieved using the following drugs: romiplostim (100%), eltrombopag (75%), cyclosporine (66.67%), mycophenolate mofetil (50%), danazol (50%) and corticosteroids (40.9%). Hemorrhagic and non-hemorrhagic complications occurred in 78.6% (n=22/28) and 28.6% (n=8/28) of the patients, respectively. Conclusion: Splenectomy remains a very efficient therapeutic modality for the treatment of ITP patients with a high percentage of splenectomy-resistant patients achieving remission. Thrombopoietin receptor agonists have shown exceptional results so far in the treatment of refractory ITP patients.